STABILITY EVALUATION OF TARTRAZINE BY LIQUID CHROMATOGRAPHY-DIODE ARRAY DETECTOR AND HIGH-RESOLUTION ELECTRON SPRAY IONIZATION QUADRUPOLE TIME-OFFLIGHT MASS SPECTROMETRY/MASS SPECTROMETRY ANALYSIS - Nagappan, Krishnaveni; Yamjala, Karthik; Sathyaseelan, Mathivathani; Byran, Gowramma (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study investigates the degradation behavior of tartrazine, a synthetic azo dye used in pharmaceutical products. Methods: For this purpose, standard solutions containing E102 were subjected to pH, oxidation, photolytic conditions and were analyzed by the developed high-performance liquid chromatography (HPLC) method. Results: The results show degradation in standard solution with the formation of single degradation product in oxidative visible light condition. The formed unknown degradation product was isolated by semipreparative HPLC and characterized using ultra-HPLC coupled with high resolution tandem mass spectrometer (MS). Conclusion: The isolated component was vacuum dried and subjected to high-resolution MS analysis for the plausible structural elucidation. Based on the fragmentation pattern of one degradation product (ODP) from their MSn studies, the ODP may be identified as 2,5-dihydroxy-1-phenyl-3- (phenyldiazenyl)-2,3-dihydro-1H-pyrazole-4-carboxylic acid. Â 